Equity and reform in mathematics education. - Goodell, Joanne E. (Curtin University, 1998)
This study focused on two themes which have recurred in education since the 1980's: equity of educational outcomes for all students and reform in mathematics education. The problem addressed in this study concerned the apparent inability of large- scale reforms to meet equity goals. The purpose of the study was to increase understanding of this problem from both theoretical and practical perspectives. The study was influenced by feminist perspectives in the choice of theoretical framework and methodology. Focusing specifically on gender equity, the study was set in the context of a large-scale reform in the USA, Ohio's Statewide Systemic Initiative, Project Discovery.There were three major objectives in this study. First was to synthesise the literature concerning gender equity in mathematics education to produce a definition of the ideal Connected Equitable Mathematics Classroom (CEMC). There were two parts to the literature review: one concerning explanations for observed gender differences in mathematics education, and another concerning initiatives implemented to try to bring about gender equity in mathematics education.The second objective was to use the definition of the ideal CEMC, derived from the literature, to determine the extent to which reform had occurred in mathematics classrooms in Ohio. This was accomplished through the analysis of quantitative data collected from a random sample of teachers and principals across the state, and qualitative data collected from seven case study sites. The third objective was to determine the barriers to and facilitators of the realisation of equity goals in middle-school mathematics classrooms involved in Project Discovery. This was accomplished through a cross-site analysis of data collected at the seven case- study sites, with the analysis framed around the characteristics of the CEMC.The outcomes of the study are set out in terms of these three objectives, culminating in a discussion of the implications and challenges which the findings of this study pose for researchers, reformers, equity advocates and practitioners.